Epidemiological Profile of Sexual Development in JIA Patients in a Tertiary Care Teaching Hospital in Eastern India - Niloy Kumar Das; Baisakhi Soren (Asian Journal of Clinical Pediatrics and Neonatology, 2017)
Background: J JIA (Juvenile Idiopathic Arthritis) is a common chronic joint disorder of childhood. In JIA puberty is often delayed. Objective of this study was to evaluate how JIA affect sexual maturity rating of children compared to control group. Subjects and Methods: A prospective study was carried out at OPD of tertiary care teaching hospital of Eastern India over 1 year. Patients diagnosed as JIA (Juvenile Idiopathic Arthritis) was included in the study as cases and age sex matched children who came for vaccination or viral fever were included as control. SMR (sexual maturity rating) was done for all. Testicular size was measured in cases of male with orchidometer. Result: 75 cases and 75 controls were included in the study. Male female ratio was 5:4. 37 (49.33%) were oligoartcular type, 20 (26.66%) were of RF negative JIA, 6 (8%) belonged to RF positive JIA.11(14.66%) patients were suffering from systemic variety where 1 (1.33%) was suffering from ERA. 17 (22.7%) had achieved SMR stage 2, on the other hand 18 (24 %) of 75 control patients achieved SMR stage 2. There was no significant difference. There was no significant difference in testicular size also. Conclusion: In prepubertal stage sexual development is not significantly affected in JIA patients compare to control group.